How do you solve these with the substitution method?

4x - y = -14

y = 8x + 7

4x - y = -14

y = 8x + 7

4x - (8x + 7) = -14 {substituted 8x + 7, in for y,into top equation}

4x - 8x - 7 = -14 {distributed negative sign through parentheses}

-4x - 7 = -14 {combined like terms}

-4x = -7 {added 7 to both sides}

x = 7/4 {divided both sides by -4}

y = 8x + 7 {bottom original equation}

y = 8(7/4) + 7 {substituted 7/4, in for x, into bottom equation}

y = 14 + 7 {cancelled and multiplied}

y = 21 {added}

**x = 7/4 and y = 21**

*© Algebra House*